PENGARUH PEMBEBANAN TERHADAP EFISIENSI DAN SUSUT UMUR TRANSFORMATOR STEP UP 6kV / 70kV DI PLTU SUMBAWA BARAT UNIT 1 DAN 2 2Ã—7 MW PT.PLN (PERSERO) UPK TAMBORA - Bayu Tiasmoro, Ilham; Wirentake; Ali Topan, Paris (Jurnal TAMBORA, 2021)
This study aims to determine the magnitude of the fluctuating load factor on the efficiency and loss of life of the 6kV/70kV transformer and to determine the optimal load in order to obtain the best efficiency and minimize loss of life. The method used in this study is a quantitative research method. The results showed that the highest efficiency of PLTU Unit 1 was at 93.3% with an output power of 5.8 MW and an input power of 6.21 MW, while the lowest was at 83.9% with an output power of 5.5 MW and a power 6.55 MW input. The highest efficiency of PLTU Unit 2 is at 95.7% with an output power of 5.5 MW and an input power of 5.75 MW, while the lowest is at 61.03% with an output power of 3.3 MW and an input power of 5.41. MW. Meanwhile, the transformer life for Unit 1 PLTU Sumbawa Barat is 0.0469 hours/day with an average load of 5.8 MW, while for Unit 2 it is 0.0311 hours/day with an average load of 5.2 MW. The size of the loss of life of the transformer depends on the given load, the greater the load, the greater the loss of life. In this case, the load for Unit 1 is higher than for Unit 2, so it can be seen that the life loss of the Unit 2 transformer is smaller. While the optimal load on the PLTU is in the position of 80-85% of its capacity. The results of this study are expected to be a material consideration for the Sumbawa power plant to better distribute and optimize the load so that there is no imbalance between the transformer capacity and the power produced and perform routine transformer maintenance to reduce losses that occur.